Gamma-Glutamyltransferase and Risk of Acute Coronary Syndrome in Young Chinese Patients: A Case-Control Study. (2nd September 2018) - Huang, Yuli; Luo, Jianjin; Liu, Xinyue; Wu, Yu; Yang, You; Li, Wensheng; Lv, Weibiao; Hu, Yunzhao
Abstract : Background . Serum gamma-glutamyltransferase (GGT) is a biomarker of hepatic disease. Recent studies have shown that GGT may also associate with the risk of coronary artery disease. However, the underlying mechanisms of this association are still unclear. Methods . This study included 216 young patients with acute coronary syndrome (aged ≤55years) and 227 age-matched controls with normal findings by coronary angiography or coronary computed tomography angiography. We use standard colorimetric techniques and sandwich enzyme-linked immunosorbent assay to measure the levels of GGT and oxidized low-density lipoprotein (ox-LDL), respectively. Traditional risk factors of coronary artery disease, including smoking, diabetes mellitus, hypertension, dyslipidemia, and obesity/overweight, were evaluated according to the current guidelines. Results . The levels of GGT were significantly correlated with body mass index and levels of triglyceride, fasting plasma glucose, aspartate aminotransferase, and ox-LDL (allP < 0.05 ). Multivariate logistic regression analysis showed that GGT was significantly associated with the risk of acute coronary syndrome in young Chinese patients (OR = 1.53, 95% CI = 1.09–2.15) after adjusting for traditional risk factors, including sex, age, quantity of smoking, hypertension, diabetes, body mass index, dyslipidemia, and high-sensitivity C-reactive protein. However, this association was significantly attenuated (OR = 1.20, 95% CI = 0.91–1.58) after further adjusting for the levels of ox-LDL. Conclusions . GGT was associated with the risk of ACS in relatively young patients. The link between GGT and the risk of ACS may be dependent on ox-LDL levels, indicating that the prooxidant action is an important pathway for GGT in the development of cardiovascular disease.